Integrative data of a novel ciliate (Alveolata, Ciliophora) propose the establishment of Heterodeviata nantongensis nov. sp. - Lijian Liao; Limin Jiang; Xiaozhong Hu (BMC Microbiology, 2024)
Abstract Background As unicellular eukaryotes, ciliates are an indispensable component of micro-ecosystems that play the role of intermediate nutrition link between bacteria or algae and meiofauna. Recent faunistic studies have revealed many new taxa of hypotrich ciliates, indicating their diversity is greater than previously thought. Here we document an undescribed form isolated from an artificial brackish water pond in East China. Examination of its morphology, ontogenesis and molecular phylogeny suggests that it represents a new species. Results The morphology and morphogenesis of the new brackish-water deviatid ciliate, Heterodeviata nantongensis nov. sp., isolated from Nantong, China, were investigated using live observations and protargol staining. The diagnostic traits of the new species include three frontal cirri, one buccal cirrus, one or two parabuccal cirri, an inconspicuous frontoventral cirral row of four to six frontoventral cirri derived from two anlagen, three left and two right marginal rows, two dorsal kineties, dorsal kinety 1 with 9–14 dikinetids and dorsal kinety 2 with only two dikinetids, and one to three caudal cirri at the rear end of dorsal kinety 1. Its main morphogenetic features are: (i) the old oral apparatus is completely inherited by the proter except undulating membranes, which are reorganized in situ; (ii) anlagen for marginal rows and the left dorsal kinety develop intrakinetally in both proter and opisthe; (iii) dorsal kinety 2 is generated dorsomarginally; (iv) five cirral anlagen are formed in both proter and opisthe; (v) in the proter, anlagen I and II very likely originate from the parental undulating membranes and the buccal cirrus, respectively, anlage III from anterior parabuccal cirrus, anlage IV originates from the parental frontoventral cirri and anlage V from the innermost parental right marginal row; and (vi) anlagen I–IV of the opisthe are all generated from oral primordium, anlage V from the innermost parental right marginal row. Phylogenetic analyses based on SSU rRNA gene sequence data were performed to determine the systematic position of the new taxon. Conclusions The study on the morphology, and ontogenesis of a new brackish-water taxon increases the overall knowledge about the biodiversity of this ciliate group. It also adds to the genetic data available and further provides a reliable reference for environmental monitoring and resource investigations.